The Subjunctive Mood in Emmanuel Macron's Presidential Speech - Wibowo, Adisah Fildan; Asnidar, Yusi; Andika, Yunilis (Franconesia, 2025)
This study aims to analyze the meaning of the subjunctive in the speech of French President Emmanuel Macron titled "Conférence des Ambassadrices et des Ambassadeurs : le discours du Président Emmanuel Macron". The research utilizes the subjunctive meaning theory proposed by Fairon & Simon (2018), Riegel et al. (2009), and Mahéo-Le Coadic et al. (2002). These theories identify 10 meanings of the subjunctive: (1) le doute (doubt), (2) la volonté/le désir/le souhaite (will/desire/wish), (3) l’ordre/la nécessité (order/necessity), (4) le sentiment (emotion), (5) la possibilité (possibility), (6) le temps (time), (7) la cause (cause), (8) le but (goal), (9) la concession/l’opposition (concession/opposition), and (10) la condition/la supposition (condition/assumption). The research adopts a qualitative approach with a content analysis method. The procedure began with identifying and downloading the data source, reading and understanding the data, formulating the research problem, seeking secondary data sources, and analyzing the data. Data collection was conducted using document analysis techniques based on Sugiyono's theory (2013). The data were analyzed using Miles and Huberman's analysis techniques (Sugiyono, 2013), which include: (1) data reduction by analyzing sentences containing the subjunctive mood in the speech text based on the main theory, (2) data presentation, and (3) drawing conclusions. The results identified 34 sentences with the subjunctive mode, consisting of 3 sentences expressing le doute (doubt), 16 sentences expressing la volonté/le désir/le souhaite (will, desire, hope), 6 sentences expressing l’ordre/la nécessité (order/necessity), 7 sentences expressing le but (goal), and 2 sentences expressing la concession/l’opposition (concession/opposition). Based on these results, this study is expected to serve as a reference in helping French language learners understand the subjunctive mood so that they can apply it correctly and accurately in daily life, both in spoken and written form. Meanwhile, there are 5 meanings that are not found in this study, namely the meaning of le sentiment (feeling), la possibilité (possibility), le temps (time), la cause (cause), and la condition/la supposition (condition/supposition).